Pengaruh Gaya Kepemimpinan Tranformasional Dan Transaksional Terhadap Komitmen Organisasi Dengan Budaya Organisasi Sebagai Variabel Intervening Pada SMK Pawyatan Daha 3 Kediri - Erik Sumarsono; Imam Baehaki (Otonomi, 2022)
The realization of organizational commitment becomes a problem in achieving organizational goals. The failure to realize organizational commitment is caused by the leadership never evaluating the results that have been achieved and the commitments made are not based on a clear consensus, and even though there is a consensus it is not implemented consistently and brings consequences as a result. an organizational culture. Researchers chose research at SMK Pawyatan Daha 3 Kediri because as an organization or educational institution that is starting to grow and develop and try to maintain its existence in the midst of competition between organizations. By experiencing two periods of leadership and having a strong organizational culture. Based on the above background, researchers are interested in conducting research with the title "The Effect of Transformational and Transactional Leadership Styles on Organizational Commitment with Organizational Culture as an Intervening Variable at SMK Pawyatan Daha 3 Kediri. This study aims to examine and prove the effect of Transformational and Transactional Leadership Styles on Organizational Commitment with Organizational Culture as an Intervening Variable at SMK Pawyatan Daha 3 Kediri. With a quantitative approach with path analysis techniques (parh analysis) using questionnaire data, with a sample of 66 respondents. In the data analysis, path analysis hypothesis tests were carried out with multiple linear analysis, classical assumptions and intervening tests. The results of the research by testing the hypothesis stated that the transformational and transactional leadership style variables had a simultaneous effect on organizational commitment. The transformational leadership style variable has a partial effect on organizational commitment. transactional variables have no partial effect on organizational commitment. transformational and transactional leadership style variables have a simultaneous effect on organizational culture. The transformational leadership style variable has a partial effect on organizational culture. transactional variables have no partial effect on organizational culture. organizational culture variables have a simultaneous effect on organizational commitment. The transformational leadership style variable has no effect on organizational commitment with organizational culture as the intervening variable and the transactional leadership style variable affects organizational commitment with organizational culture as the intervening variable.